Leadership of School’s Headmaster in Taking Decision of Curriculum Development in The State Elementary School (SDN) 101786 Helvetia, Deli Serdang District - Nurtuah Tanjung; Nurika Khalila Daulay (Britain International for Academic Research (BIAR) Publisher, 2019)
This study aims to describe the principal's leadership in decision-making curriculum development at Elementary School 101786 Helvetia Research includes principal leadership, decision-making, and curriculum development. This research uses qualitative research type with case study approach. The location of the research is Elementary School 101786 Helvetia District Labuhan Deli Deli Serdang Regency North Sumatra Province Source. The method according to the title of this study researchers using qualitative approach, the data in this study is, principals, teachers, school committee. The conclusions of this research are: 1. Leadership of principal in decision making of curriculum development at elementary school 101786 Helvetia